Organic milpa: yields of maize, beans, and squash in mono- and polycropping systems - Ebel, Roland; Pozas Cárdenas, José Gonzalo; Soria Miranda, Florencio; Cruz González, Jesús (REVISTA TERRA LATINOAMERICANA, 2017)
The milpa is a traditional Mesoamerican production system based on polycropping corn (Zea mays L.), squash (Cucurbita spp.), and bean (Phaseolus vulgaris L.). Milpa is characterized by synergetic interactions between these plants that favor the total output of this arrangement and increase resilience to perturbations of the entire agroecosystem. Still, current environmental and socio-economic threats decrease the milpa’s attractiveness for farmers. Therefore, innovations of milpa are necessary but should not affect its principal strength: its agrobiodiversity. In Piedras Blancas, central Mexico, in 2015, an experiment was carried out to compare all possible combinations of maize, squash, and bean polyculture. Crop management was based on the principles of organic farming and fertilization was provided using manure compost. The combination of maize and beans achieved higher total production, in which maize yielded 7.9 Mg ha‑1 and beans 1.9 Mg ha‑1. In this maize-bean polyculture, each maize plant produced 68.3 g, 1.2 times higher than the yield per plant in monoculture and each bean plant yielded 27.5 g, which was equal to its performance in monocropping. All other combinations of crops (maize-squash, bean-squash, and maize-bean-squash) also exceeded their respective monocultures in terms of total production. As regards squash, it was revealed that the diverse associations increased its yield per plant, but per plant production of maize and beans decreased when they were associated with squash. The overyielding of maize and beans in association, compared with their respective monocultures, highlights the potential of polycropping systems to provide satisfactory yields for all involved crops.